2024
DOI: 10.1186/s41983-023-00775-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the molecular web of Alzheimer’s disease: unveiling pathways for effective pharmacotherapy

Devika Jadhav,
Nikita Saraswat,
Neeraj Vyawahare
et al.

Abstract: Introduction Alzheimer’s disease is a neurocognitive disorder that affects elderly people by slowly impaired cognition, dementia, and gets worse with age. It slowly impacts the quality of life. Clinically, it is distinguished by a transition from episodic memory to a gradual reduction in cognitive ability leading to cognitive dysfunction. Neurofibrillary tangles and amyloid plaques are unique structures that are thought to have a role in the pathogenesis of Alzheimer's disease. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…The gender-specific effect was found, whereby the interaction between COMT and APOE was more prominent in female individuals who have been diagnosed with AD (Reynolds et al, 1999). On the other hand, the male population with MCI demonstrated the greatest level of synergy between the aforementioned pair of genes (Jadhav et al, 2024). Another study reported a correlation between COMT rs4680 alleles and sporadic AD in males (Dunk et al, 2023).…”
Section: Investigates the Potential Association Between Estrogen Estr...mentioning
confidence: 96%
See 1 more Smart Citation
“…The gender-specific effect was found, whereby the interaction between COMT and APOE was more prominent in female individuals who have been diagnosed with AD (Reynolds et al, 1999). On the other hand, the male population with MCI demonstrated the greatest level of synergy between the aforementioned pair of genes (Jadhav et al, 2024). Another study reported a correlation between COMT rs4680 alleles and sporadic AD in males (Dunk et al, 2023).…”
Section: Investigates the Potential Association Between Estrogen Estr...mentioning
confidence: 96%
“…The identification of pharmacological interventions that target ERα is considered a critical element in the preservation of neuronal function and the prevention of neurodegeneration (Wang et al, 2024). The neuroprotective properties of E2 and SERMs, namely, tamoxifen and raloxifene, have been documented in human neuronal cells (Jadhav et al, 2024). The aforementioned compounds have demonstrated an ability to enhance resistance against the toxic effects induced by Aβ (Plascencia-Villa & Perry, 2020).…”
Section: Targeting Ersmentioning
confidence: 99%
“…Some of these include Gosuranemab, Tilavonemab, Semorinemab, Zagotenemab, Aducanumab [210], Lecanemab [211], and anti-tau antibodies, which have shown significant improvement in patients at early stages [20]. However, vaccines targeting the tau protein, such as the anti-tau vaccine (AADvac1) and ACI-35, are yet to demonstrate thera-peutic outcomes [212,213]. Additionally, pharmacological treatments such as donepezil, galantamine, rivastigmine, and memantine are currently available drugs that mostly inhibit acetylcholinesterase and activate NMDA receptors, offering symptomatic relief in AD [20,212,214].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%